Xenia umbellata (Octocorallia): A novel model organism for studying octocoral regeneration ability - Nadir, Elinor; Lotan, Tamar; Benayahu, Yehuda (Frontiers in Marine Science, 2023)
Climate change is leading to phase shifts in coral reefs worldwide. In many biogeographic regions, octocorals are now becoming the most abundant benthic components, due to their environmental resilience and ability to rapidly colonize reef surfaces. Regeneration abilities and asexual reproduction are highly important for this ability and probably contribute to the successful spread of certain octocorals, including invasive species. Regeneration, however, has been little investigated in octocorals. To achieve a deeper understanding of octocoral regeneration, we employed Xenia umbellata, a common octocoral in the Red Sea, as a novel experimental model for laboratory studies. Using single-polyp modules, we investigated its regeneration ability and polyp asexual reproduction (budding). Excised polyps successfully reattached to tissue-culture plates within 2-3 days and started budding within 10 days. Amputation of the oral disc led to full regeneration within 7-10 days, with budding continuing throughout this period. Moreover, amputated tentacles developed into polyps within 21 days, demonstrating an unusual capacity for whole-body regeneration. The regeneration abilities of this species imply high totipotency of all polyp parts and are likely important for its life cycle. Further research using this model is expected to enhance the ecological and molecular understanding of octocoral development and provide insights into phase shifts currently occurring in coral reefs. Our study also suggests that X. umbellata has potential as a model organism for integrative studies on regeneration, physiology, developmental biology, and more, encouraging its adoption as a novel colonial cnidarian model organism.